The Birth Order and Personalities of Medical Students - Chan-ob T. (2014)
The purpose of this study was to determine how birth position i.e. first-born, middle-born, lastborn, and only child, correlates with personality. Material and Method : One hundred and eighty from 186 (97%) 1st year medical students of Chiang Mai Medical School were asked to complete a questionnaire and take a personality test. The data obtained included age, sex, Grade Point Average (GPA), and family background i.e. birth order and the students' personality profiles, which were assessed by the California Psychological Inventory (CPI). Results: The results showed that only children and lastborn had more positive personality factors than other groups. They had more ambition, breadth of interests, versatility, self confidence, clear-thinking, intelligence, and independence than first-born and middle-born (Cs and Ai scale on CPI). In addition, the students whose parents had died, separated, or divorced had some personality profiles that differed from the others. The findings both supported and contradicted other papers.